Functional roles of the thalamus for language capacities - Klostermann, Fabian; Ehlen, Felicitas (Frontiers in Systems Neuroscience, 2013)
Early biological concepts of language were predominantly corticocentric, but over the last decades biolinguistic research, equipped with new technical possibilities, has drastically changed this view. To date, connectionist models, conceiving linguistic skills as corticobasal network activities, dominate our understanding of the neural basis of language. However, beyond the notion of an involvement of the thalamus and, in most cases also, the basal ganglia in linguistic operations, specific functions of the respective depth structures mostly remain rather controversial. In this review, some of these issues shall be discussed, particularly the functional configuration of basal network components and the language specificity of subcortical supporting activity. Arguments will be provided for a primarily cortico-thalamic language network. In this view, the thalamus does not engage in proper linguistic operations, but rather acts as a central monitor for language-specific cortical activities, supported by the basal ganglia in both perceptual and productive language execution.